Variable stoichiometry of phosphate-linked anion exchange in Streptococcus lactis: implications for the mechanism of sugar phosphate transport by bacteria. - Ambudkar, S V (1986)
Phosphate/2-deoxyglucose 6-phosphate antiport in Streptococcus lactis showed an exchange stoichiometry that varied over a 2-fold range when assay pH was shifted between pH 8.2 and pH 5.2. At pH 7.0 and above, 2 mol of phosphate moved per mol of sugar phosphate; at pH 6.1 the ratio was 1.5:1, while at pH 5.2 the overall stoichiometry fell to 1.1:1. This pattern was not affected by valinomycin in potassium-based media, nor could variable stoichiometry be attributed to altered hydrolysis of the sugar phosphate substrate. In kinetic studies at pH 7.0 or pH 5.2, sugar 6-phosphate was a competitive inhibitor of phosphate transport, indicating operation of a single system. Parallel tests showed that the affinity of antiport for its sugar 6-phosphate substrate was insensitive to pH in this range. Overall, such results suggest a neutral exchange that has specificity for monovalent phosphate but that selects randomly among the available mono- and divalent sugar 6-phosphates. A simple model that shows this behavior suggests a mechanistic role for anion exchange in bacterial transport of sugar phosphate or other organic anions.